Primary production in the southern Gulf of Mexico estimated from solar-stimulated natural fluorescence - Aguirre Gómez, Raúl (HIDROBIOLÓGICA, 2017)
This papaer reports a study on the horizontal and vertical chlorophyll and primary production distributions. Chlorophyll a concentrations were calcuated from natural fluorescence during th fall season of 1997 in the southern part of the Gulf of Mexico. It was found a neraly homogeneous distribution of chlorophyll (0.4 to 2.3 mg m-3) and primary production (1.2 to 6.7 mg C m-3 h-1) at oceanic areas, but conspicuosly different values at coastal or sediment-laden zones (12.5 - 46.6 mg m-3 for chlorophyll and 34 - 120 mg C m-3 h-1 for production). The results obtained from solar stimulated natural fluorescence are similar to those calculated by other authors using different methods. This method provides reliable results and can be alternatively used.